Resistência cultural afro-descendente na zona leste de São Paulo: o movimento negro "Fala Negão Fala Mulher" (1980-2008) - Paulo, João Pereira (2008)
In the present work I analyze the construction of conceptions of pertaining and ancestry among groups african-descendants, more specifically the negro movement Fala Negão Fala Mulher. The trajectory of these people that seek to support theirs cause on culture, theirs modes and practice in theirs experience of life. Having the city of São Paulo as place of theirs live deeply and contradictions, in the dislocation between the downtown and the distant suburb. The questions argued in this work seek to reflect on the arguments that integrate the people who live in the communities of the zone east of city of São Paulo, taking in consideration aspects how knowledge and makings in theirs experiences. The disputes and struggle for the housing and modes of experience of life the proper reality confronting problems with transport, security and health. The discussion about the zone east and the different forms to act inside of the community, already the zone east produces and provides different ethnics and economics groups. The districts of Itaquera, Guaianases and São Matheus are target of the reflections pass by question of pertaining and in the forms that if relate. All this work is based at discussion about culture african-descendant in theirs manifestations of signified and re-signified, exploring the carnival and the construction of the tensions between the social movements in the zone east